Behavior of Sitophilus zeamais(Coleoptera: Curculionidae) to hydrolate of Senna spectabilis (Fabaceae) - Teixeira, Gisele dos Santos Silva (2023)
Sitophilus zeamais is considered plausibly of economic importance in corn storage, as it makes the grain unfeasible. Management with the use of products from bioactive plants has been highlighted in the management of estimates, therefore, this work aimed to evaluate the behavioral response of S. zeamais to exposure to Senna spectabilis hydrolate at different concentrations to identify stimuli attractive or repulsive. The bioassays were carried out at the LEA of UFAPE, for which they were obtained after the leaves of Senna spectabilis were dried, ground and subjected to hydrodistillation. The hydrosol obtained was separated by density and stored in an amber glass bottle in a refrigerator. Diluted and used in a four-way olfactometer coupled to a vacuum pump to perform the behavioral test, 10 µl of concentrations of 0.01, 0.1 and 1% of hydrolate in Hexane were applied to its extremities. One insert at a time was presented for 15 minutes, with 20 repetitions. The data obtained were submitted to static analyses, performed by the T test, where a significance level (P<0.05) was adopted. The results of the olfactometry tests demonstrate that the S. spectabilis hydrolate from leaves diluted in hexane (0.10 and 1.00%) showed attractiveness under S. zeamais.